Sonication accelerated formation of Mg-Al-phosphate layered double hydroxide via sol-gel prepared mixed metal oxides - Sokol, Denis (2019)
Single-phase magnesium-aluminium layered double hydroxide (LDH) intercalated with dihydrogen phosphate was successfully produced by hydration of nanopowder of the respective mixed metal oxide (MMO) obtained using sol-gel based method followed by a two-step anion exchange hydroxide-to-chloride and chloride-to-phosphate. The MMO with the metal cation ratio of Mg/Al = 2:1 was prepared using the aqueous sol-gel method. Processes of the parent Mg2Al-OH LDH formation and the successive anion-exchanges, ОН- → Cl- and Cl- → H2PO4-, were considerably accelerated via the application of high-power (1.5 kW) ultrasound. The crystalline phases formed at all stages of the Mg2Al-H2PO4 LDH production were characterized using X-ray diffraction, scanning electron microscopy, scanning transmission electron microscopy, inductive coupled plasma optical emission spectroscopy, Fourier transform infrared spectroscopy, and thermogravimetric analysis. Based on the data of chemical analysis and the XRD data, the type of the intercalated phosphate anion was determined and the arrangement of this anion in the interlayer was modelled.